Bread characteristics and antioxidant activities of Maillard reaction products of white pan bread containing various sugars. (September 2018) - Shen, Yanting; Chen, Gengjun; Li, Yonghui
Abstract: Melanoidins are brown colored compounds formed during Maillard reaction. Bread is a staple food for most of the population and is a major source of dietary melanoidins. The objective of this study was to investigate physical properties, melanoidin content and antioxidant capacity of white pan bread as related to sugar types and amount as well as baking conditions. Bread crust color, melanoidin content and antioxidant capacity were positively affected by increasing baking time and temperature and sugar amount. Increasing baking time was more effective in enhancing the antioxidant activity compared with increasing baking temperature for all the breads in the same sugar group. Ribose was the most effective in improving the melanoidin content and DPPH radical scavenging activity of bread crust compared with other sugars; however, breads with ribose had smaller loaf volume and harder crumb texture. Color and melanoidin content of bread crust had partial positive relationship with the antioxidant capacity of the white pan bread. Overall, breads with sucrose or fructose had a good balance of loaf volume and antioxidant capacities. This study provides useful information towards understanding and manipulating MRPs formation to maximize antioxidant potential in bread products. Highlights: Breads with fructose or sucrose had larger loaf volume and softer crumb texture. Antioxidant activity of bread crust was enhanced with the addition of sugars. Antioxidant activity increased with baking time, temperature or sugar amount. Browning intensity only partially responsible for bread antioxidant capacity.